The Influence of the Scientific-Based Self-Regulated (SBSR) Bilingual Module in Improving Students’ Knowledge - Irma, Irma; Agusta, Erie; Nuraini, Nita; Kholillah, Kholillah (Jurnal Penelitian dan Pembelajaran IPA, 2021)
The objectives of this study were 1) to find out whether there was an influence of the learning of the scientific-based self-regulated (SBSR) bilingual module in improving the cognitive abilities of the tenth grade students of Biology subjects, and 2) to find out how the percentage comparison of the influence between the learning of scientific-based self-regulated (SBSR) bilingual module class with conventional learning class in improving cognitive of the tenth grade students of Biology subjects. The research method used the quasi-experimental using the non-equivalent control group design. The data was analyzed through paired sample t test and omega index. The results of this study showed that 1) there was an increase in cognitive ability of the tenth grade students through the use of the learning of scientific-based self-regulated (SBSR) bilingual module on Biology subject. 2) There was an increase in cognitive ability of the tenth grade students through the conventional learning on Biology subject, and 3) the percentage of SBSR bilingual module influence was higher (60%) compared with conventional learning class with discovery learning influence (4.7%) in improving students' cognitive.